Interference alignment in wireless communication systems: precoding design, scheduling and channel imperfections - Bandeira, Carlos Igor Ramos (2012)
In multiuser MIMO systems, the transmitter can select a subset of antennas and/or users which have good channel conditions to maximize the system throughput using various selection criteria. Furthermore, precoding can provide free interference dimensions. The Interference Alignment (IA) is based on the concept of precoding and it offers different trade-offs between complexity and performance. The basic idea of Interference Alignment consists in precoding the transmitted signals such that they are aligned at the receiver where they constitute interference, while at the same time disjointed from the desired signal. However, the Channel State Information (CSI) has been a concern because it impacts the performance of IA algorithms. Hence, we propose to analyze the performance of antenna selection and multiuser diversity together in order to allow opportunistic IA using several criteria over the disturbance of CSI. Analyses and simulations verify the behavior of the proposed scheme.